2019
DOI: 10.1002/hbm.24740
|View full text |Cite
|
Sign up to set email alerts
|

Patterned functional network disruption in amyotrophic lateral sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease primarily affecting motor function, with additional evidence of extensive nonmotor involvement. Despite increasing recognition of the disease as a multisystem network disorder characterised by impaired connectivity, the precise neuroelectric characteristics of impaired cortical communication remain to be fully elucidated. Here, we characterise changes in functional connectivity using beamformer source analysis on resting‐state elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
64
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 78 publications
13
64
1
Order By: Relevance
“…It is reported to be decreased in the alpha (8)(9)(10)(11)(12)(13) band in AD subjects by multiple studies but some other studies have additionally reported an increase in delta (0.5-4 Hz) band coherence [18,19] and an increase in theta (4-8 Hz) band coherence [20]. In another comparison of AD and cognitively normal patients, both the phase lag index (PLI) and imaginary coherence showed a decrease in functional connectivity in the beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) frequency band [21], where other studies showed differences in the alpha band PLI [22] and alpha [23] but also delta and theta band [24] imaginary coherence.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…It is reported to be decreased in the alpha (8)(9)(10)(11)(12)(13) band in AD subjects by multiple studies but some other studies have additionally reported an increase in delta (0.5-4 Hz) band coherence [18,19] and an increase in theta (4-8 Hz) band coherence [20]. In another comparison of AD and cognitively normal patients, both the phase lag index (PLI) and imaginary coherence showed a decrease in functional connectivity in the beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) frequency band [21], where other studies showed differences in the alpha band PLI [22] and alpha [23] but also delta and theta band [24] imaginary coherence.…”
Section: Introductionmentioning
confidence: 94%
“…The freely available 'Brainwave' software [40] was used to estimate functional connectivity. Mean global coherence (Coh), imaginary coherence (iCoh), phase locking value (PLV), amplitude envelope correlation (AEC), AEC with leakage correction (AEC-c), phase lag index (PLI) and weighted PLI (wPLI) were estimated in five frequency bands: broadband (0.5-30 Hz), delta (0.5-4 Hz), theta (4-8 Hz), alpha (8-13 Hz) and beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Functional connectivity per electrode was estimated by averaging the values for each possible electrode pair per electrode (for example, the value of electrode Fp1 is the average of each potential electrode pair with electrode Fp1).…”
Section: Eeg Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The new implementation of EBI was applied on reallife experimental High-Density EEG data to further demonstrate the utility in practice. The experimental EEG was recorded during steady state conditions, including a resting-state condition (S. Dukic et al, 2017;Stefan Dukic et al, 2019) and a sustained isometric motor task (Coffey et al, 2019). The data included 363 and 99 epochs of 1 second duration in each condition respectively.…”
Section: Exemplary Application On Experimental Datamentioning
confidence: 99%
“…Many studies have compared electrophysiological signatures from ALS patients and controls (Jayaram et al 2015;Nasseroleslami et al 2019;Dukic et al 2019;Maruyama et al 2020), reporting features distinguishing the two groups. The most reliable evidence found is a decrease in alpha relative power, with a shift of the peak in the alpha frequency band (generally present in healthy patients' EEG power spectrum) to lower frequencies (Mai et al 1998;Hohmann et al 2018).…”
Section: Introductionmentioning
confidence: 99%